Design of self-healing catalysts for aircraft application. Issue 6 (3rd December 2018) - Calabrese, Elisa; Longo, Pasquale; Naddeo, Carlo; Mariconda, Annaluisa; Vertuccio, Luigi; Raimondo, Marialuigia; Guadagno, Liberata
Abstract : Purpose: The purpose of this paper is to highlight the relevant role of the stereochemistry of two Ruthenium catalysts on the self-healing efficiency of aeronautical resins. Design/methodology/approach: Here, a very detailed evaluation on the stereochemistry of two new ruthenium catalysts evidences the crucial role of the spatial orientation of phenyl groups in the N-heterocyclic carbene ligands in determining the temperature range within the curing cycles is feasible without deactivating the self-healing mechanisms (ring-opening metathesis polymerization reactions) inside the thermosetting resin. The exceptional activity and thermal stability of the HG2MesPhSyn catalyst, with the syn orientation of phenyl groups, highlight the relevant potentiality and the future perspectives of this complex for the activation of the self-healing function in aeronautical resins. Findings: The HG2MesPhSyn complex, with the syn orientation of the phenyl groups, is able to activate metathesis reactions within the highly reactive environment of the epoxy thermosetting resins, cured up to 180°C, while the other stereoisomer, with the anti-orientation of the phenyl groups, does not preserve its catalytic activity in these conditions. Originality/value: In this paper, a comparison between the self-healing functionality of two catalytic systems has been performed, using metathesis tests and FTIR spectroscopy. In the field of the design of catalytic systems for self-healing structural materials, a very relevant result has been found: a slight difference in the molecular stereochemistry plays a key role in the development of self-healing materials for aeronautical and aerospace applications.